TEMPORAL BEHAVIOR OF NDVI MEASURED WITH AN ACTIVE OPTICAL SENSOR FOR DIFFERENT VARIETIES OF SUGARCANE - FRASSON, FLÁVIA R.; MOLIN, JOSÉ PAULO; POVH, FABRÍCIO P.; SALVI, JOSÉ VITOR (Revista Brasileira de Engenharia de Biossistemas, 2007)
Activeoptical sensors are a new approach for site specific nitrogen management on real time andthey have been successfully used on grain crops. This work consisted in evaluating the behaviorof the Normalized Difference Vegetation Index (NDVI) using a commercial active optical sensor on28 sugarcane varieties, as well as analyzing the temporal behavior of this index for each varietythroughout the initial 150 days of their productive cycle. The NDVI data was collected with 90, 120and 150 days after planting (DAP). A descriptive statistical analysis of the data was performed anda Tukey test was applied to contrast the NDVI means. Results indicated that the varieties interferein the NDVI readings and, in general, the readings with 90 DAP were different from those with 120and 150 DAP, tending to stabilize along time for each variety.